Time required to start multicentre clinical trials within the Italian Medicine Agency programme of support for independent research. Issue 10 (11th June 2015) - De Feo, Gianfranco; Frontini, Luciano; Rota, Silvia; Pepe, Antonio; Signoriello, Simona; Labianca, Roberto; Sobrero, Alberto; De Placido, Sabino; Perrone, Francesco
Abstract : Background and aim: Time allowed for independent ethics committees (IECs) and administrative offices to assess and activate clinical trials is regulated by law. This study aims to describe time spent activating two multicentre non-profit trials supported by the Italian Medicines Agency (AIFA). Five non-AIFA supported (NAS) trials were used as a benchmark. Methods: The two AIFA-supported trials were FATA-GIM3 (optimal adjuvant hormonal treatment for breast cancer) and TOSCA (duration of adjuvant FOLFOX in colorectal cancer). The five NAS trials focused on lung or ovarian cancer. The following were measured for all trials: date of submission of trial documentation to peripheral IEC, date of IEC opinion and date trial contracts were signed. Times are reported in months. Results: 106 centres applied to participate in FATA-GIM3 and 137 in TOSCA. An IEC opinion was issued by 100/106 (1 negative opinion) and 137/137 (2 negative opinions) centres, with a median time from submission of 3.6 months (range 0.1–60.2). After a positive IEC opinion, the median time before signing the trial contract was 3.3 months (0.1–59.2). Contracts were signed with 93/99 and 135/135 centres, with a median time from submission of study documentation of 8.4 months (0.5–61.1). Times for NAS trials were not substantially different. Conclusions: FATA-GIM3 and TOSCA centres were opened after a median of 8 months, consisting of nearly 4 months each for IEC opinion and administrative signature, similar to the NAS trials. The process of trial activation in Italy remains inefficient and takes far longer than legally allowed.